Strategi Untuk Meningkatkan Niat Menggunakan Asuransi Syariah - Kartika, Meri; H, Herlinda; J, Julina (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to determine strategies to increase intentions to use sharia insurance. This research uses a literature study or library research method. The results of this research show that there are several ways that can be used to increase consumers' intention to use sharia insurance, namely, increasing human resources for sharia insurance agents, government regulatory support, and several factors that influence the intention to use sharia insurance, namely, among others, consumer trust and purchase intention.